Acute Alcohol Intoxication Inhibits Bystander Intervention Behavior for Sexual Aggression Among Men with High Intent to Help - Leone, Ruschelle M. (Alcohol Clin Exp Res, 2018)
BACKGROUND: Bystander training programs aim to encourage third-party witnesses to intervene in high-risk sexual situations; however, these programs rarely focus on training bystanders to effectively intervene when intoxicated. This is not surprising due to the limited evidence on the proximal effects of alcohol on bystander intervention for sexual aggression. To this end, the aim of the present study was to test the effects of men’s self-reported intent to help strangers and acute alcohol intoxication on the likelihood and speed of sexual aggression intervention. METHODS: Participants were 74 men who completed a measure of intent to help (Session 1) and were randomly assigned to consume alcohol or a no-alcohol control beverage (Session 2). Next, they engaged in a novel laboratory paradigm in which they and four confederates (two men, two women) watched a female confederate, who reported a strong dislike of sexual content in the media, view a sexually explicit film which they could stop at any time. Bystander intervention was operationalized as whether and how quickly participants stopped the film. RESULTS: Findings indicated that (1) intent to help strangers predicted faster sexual aggression intervention, and (2) intent to help strangers predicted a higher likelihood and faster rate of sexual aggression intervention among sober, but not intoxicated, men. This latter finding suggests that among men who endorsed a high willingness to intervene in sexual aggression, alcohol intoxication decreased intervention behavior. CONCLUSIONS: Results demonstrate that alcohol functions as a barrier to intervention for men who would otherwise intervene. Findings are interpreted using an integrative framework for intoxicated sexual aggression intervention and highlight the need for bystander training programs to incorporate alcohol interventions to reduce heavy drinking and psychoeducation to train bystander how to intervene when intoxicated.